Body condition and evolution of maturation of Atlantic cod in Newfoundland - Baulier, Loïc; Heino, Mikko; Lilly, George R.; Dieckmann, Ulf (ICES, 2006)
Atlantic cod (Gadus morhua, L.) stocks off Newfoundland and Labrador underwent severe depletions that started in the late 1980s and led to moratoria in the early 1990s. Fisheries closures are still applied in most of the areas where cod is found. A very low stock level, probably resulting from the combined effects of overfishing and unfavorable environmental conditions, has been accompanied with modifications of life history traits of the fish. Among reproductive traits, a decrease in both age and size at first reproduction has been observed. A partial genetical determinism of these shifts is supported by earlier analyses of probabilistic maturation reaction norms, revealing a consistent trend towards earlier maturation but also strong short-term fluctuations. In this study, we elucidate the effect of changes in individual body condition on short and long-term changes in maturation of cod. Laboratory studies have demonstrated that condition of individuals can influence the number and quality of offspring in cod. Here we use probabilistic maturation reaction norms with three explanatory dimensions (age, size and condition) to examine to what extent changes in age- and size-dependent maturation probabilities are linked with changes in condition, as measured by the hepato-somatic index.